2019
DOI: 10.1039/c8ta10585e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin, lightweight and flexible perovskite solar cells with an excellent power-per-weight performance

Abstract: Ultralight and flexible perovskite solar cells with the orthogonal AgNW electrodes exhibit an excellent power-per-weight of 29.4 W g−1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
107
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 48 publications
0
107
0
Order By: Relevance
“…Unfortunately, due to the feature of brittleness, ITO electrode does not demonstrate perfect performance in flexible photoelectric devices. Although some flexible transparent electrodes such as silver nanowires and carbon nanotubes have shown the potential for application in flexible PSCs, they have not made outstanding progress in device efficiency, especially in the large-area devices [34][35][36][37][38][39] . Therefore, flexible PSCs based on the modified ITO electrode are also worth for further investigation.…”
mentioning
confidence: 99%
“…Unfortunately, due to the feature of brittleness, ITO electrode does not demonstrate perfect performance in flexible photoelectric devices. Although some flexible transparent electrodes such as silver nanowires and carbon nanotubes have shown the potential for application in flexible PSCs, they have not made outstanding progress in device efficiency, especially in the large-area devices [34][35][36][37][38][39] . Therefore, flexible PSCs based on the modified ITO electrode are also worth for further investigation.…”
mentioning
confidence: 99%
“…While totally flexible photovoltaic devices have improved, they are still not at the desired level. For instance, power conversion efficiencies of 4.2, 12.85, and 10% have been reported for ultra-flexible organic, perovskite, and quantum dot solar cells with power-per-weight output with values of 10, 29.4, and 6.5 W g −1 , respectively (Kaltenbrunner et al, 2012;Zhang et al, 2017;Kang et al, 2019); demonstrating the still evident gap in efficiency when compared to devices not focused on flexibility. It is worth-noting, that in all three cases, the strategy to enhance the light weight, stretchability and stability of the device, was focused on shifting from glass substrates to more flexible polymers in junction with AgNWs.…”
Section: Applications Photovoltaicsmentioning
confidence: 99%
“…It has been demonstrated that Graphene, a single layer of carbon atoms closely packed into a honeycomb twodimensional (2D) lattice (Novoselov et al, 2004), has potential for flexible electrochemical energy storage device applications due to its outstanding characteristics of chemical stability, high electrical conductivity and large surface area (Yan Wang et al, 2009). Applied into supercapacitors, it has been employed as an electrode when coupled with a wide variety of materials like cellulose (Pushparaj et al, 2007;Xing et al, 2019), polyaniline (de Souza Augusto et al, 2018;Kang et al, 2019), metallic foams (Gao et al, 2018;Manjakkal et al, 2018;Taniya Purkait, 2018) and aerogels (Bora et al, 2018) rendering overall promising results. Similarly, flexible Li-Ion batteries have also used carbon nanotubes as electrodes combined with graphene foams (Ren et al, 2018), carbon fibers , metal-oxides (Guo et al, 2019;Bubulinca et al, 2020) and nanoparticles (Yuan et al, 2018).…”
Section: Energy Storagementioning
confidence: 99%
“…Along with, the mechanical stability of the device is also essential to generate adequate power per weight for their utilization. The potential of reaching extremely high specific powers in PSC reporting ~29.4 W•g −1 with only 12% efficient device as demonstrated by Kang et al (2019) [205]. This However, stability was encountered as the most challenging for PSC efforts, were given to characterize it at the outdoor condition.…”
Section: Lightweight Pscs For Bipvmentioning
confidence: 99%